Value added medicines: what value repurposed medicines might bring to society? - Mondher Toumi; Cécile Rémuzat (Taylor & Francis Group, 2017)
Background & objectives: Despite the wide interest surrounding drug repurposing, no common terminology has been yet agreed for these products and their full potential value is not always recognised and rewarded, creating a disincentive for further development. The objectives of the present study were to assess from a wide perspective which value drug repurposing might bring to society, but also to identify key obstacles for adoption of these medicines and to discuss policy recommendations. Methods: A preliminary comprehensive search was conducted to assess how the concept of drug repurposing was described in the literature. Following completion of the literature review, a primary research was conducted to get perspective of various stakeholders across EU member states on drug repurposing (healthcare professionals, regulatory authorities and Health Technology Assessment (HTA) bodies/payers, patients, and representatives of the pharmaceutical industry developing medicines in this field). Ad hoc literature review was performed to illustrate, when appropriate, statements of the various stakeholders. Results: Various nomenclatures have been used to describe the concept of drug repurposing in the literature, with more or less broad definitions either based on outcomes, processes, or being a mix of both. In this context, Medicines for Europe (http://www.medicinesforeurope.com/value-added-medicines/) established one single terminology for these medicines, known as value added medicines, defined as 'medicines based on known molecules that address healthcare needs and deliver relevant improvements for patients, healthcare professionals and/or payers'. Stakeholder interviews highlighted three main potential benefits for value added medicines: (1) to address a number of medicine-related healthcare inefficiencies related to irrational use of medicines, non-availability of appropriate treatment options, shortage of mature products, geographical inequity in medicine access; (2) to improve healthcare system efficiency; and (3) to contribute to sustainability of healthcare systems through economic advantages. Current HTA framework, generic stigma, and pricing rules, such as internal reference pricing or tendering processes in place in some countries, were reported as the current key hurdles preventing the full recognition of value added medicines' benefits, discouraging manufacturers from bringing such products to the market. Discussion & conclusions: There is currently a gap between increasing regulatory authority interest in capturing value added medicines' benefits and the resistance of HTA bodies/payers, who tend to ignore this important segment of the pharmaceutical field. This situation calls for policy changes to foster appropriate incentives to enhance value recognition of value added medicines and deliver the expected benefit to society. Policy changes from HTA perspective should include: absence of any legislative barriers preventing companies from pursuing HTA; HTA requirements proportionate to potential reward; HTA decision-making framework taking into account the specific characteristics of value added medicines; eligibility for early HTA dialogues; Policy changes from pricing perspective should encompass: tenders/procurement policies allowing differentiation from generic medicines; eligibility for early entry agreement; non-systematic implementation of external and internal reference pricing policies; recognition of indication-specific pricing. At the same time, the pharmaceutical industry should engage all the stakeholders (patients, healthcare providers, HTA bodies/payers) in early dialogues to identify their expectations and to ensure the developed value added medicines address their needs.